You are on page 1of 14

ECE 307

Fourier Transform
Z. Aliyazicioglu
Electrical & Computer Engineering Dept.
Cal Poly Pomona

Fourier Transform
The Fourier transform (FT) is the extension of the Fourier series to
nonperiodic signals. The Fourier transform of a signal exist if
satisfies the following condition.

x(t ) dt <

The Fourier transform

X ( ) =

x(t )e

j t

dt

The inverse Fourier transform (IFT) of X() is x(t)and given by

x(t ) =

1
2

X ( )e

j t

Fourier Transform
Also, The Fourier transform can be defined in terms of frequency of
Hertz as

X (f ) =

x(t )e

j 2 ft

dt

and corresponding inverse Fourier transform is

x(t ) =

X (f )e

j 2 ft

df

Fourier Transform
Example:

Determine the Fourier transform of a rectangular pulse


shown in the following figure
x(t)
h

a
j
j 2a

e 2
e

a / 2
a
sin( )
2h
a
2
sin( ) = ha
=
a
2

2
a
= ha sinc

X ( ) =
t
-a/2

a/2

a/2

he jt dt =

h
j

Fourier Transform
Example:

To find in frequency domain,


2 fa
j
j 22fa

e 2
e

a / 2
sin( fa)
h
=
sin( fa) = ha
f
fa
= ha sinc ( fa )
a/2

X (f ) =

he j 2 ft dt =

h
j 2 f

h = 1,
a =1

X ( ) = 2sinc

>>
>>
>>
>>
>>
>>
>>
>>
>>

h=1;
a=1;
f=-3.5:0.01:3.5;
w=2*pi*f;
x=h*a*sinc(w*a/(2*pi));
plot (w,x)
title ('X(\omega)')
xlabel('\omega');

Fourier Transform
h = 1,
a=2
2
X ( ) = 2sinc

2
>>
>>
>>
>>
>>
>>
>>
>>
>>
>>
>>
>>
>>
>>

h=1;
a=1;
f=-3.5:0.01:3.5;
w=2*pi*f;
x=abs(h*a*sinc(w*a/(2*pi)));
subplot (2,1,1)
plot (w,x)
title ('|X(\omega)|')
xlabel('\omega')
xp=phase(h*a*sinc(w*a/(2*pi)));
subplot (2,1,2)
plot (w,xp)
title ('phase X(\omega)')
xlabel('\omega')

Fourier Transform
Example
Determine the Fourier transform of the Delta function (t)

X ( ) =

(t )e

j t

dt = e j 0 = 1

X()
1

Fourier Transform
Properties of the Fourier Transform
We summarize several important properties of the Fourier Transform as follows.

1. Linearity (Superposition)
x1(t ) X 1( )

If

Then,

Proof:

and

x2 (t ) X 2 ( )

a1x1(t ) + a2 x2 (t ) a1X1( ) + a2 X 2 ( )

j t
j t
j t
[a1x1(t ) + a2 x2 (t )] e dt = a1 x1(t )e dt + a2 x2 (t )e dt

= a1X 1( ) + a2 X 2 ( )

Fourier Transform
Properties of the Fourier Transform
2. Time Shifting
If

x(t ) X ( )

x(t t0 ) X ( )e jt0

Then,

Proof:

Let = t t0

then t = + t0

x(t t0 )e jt dt =

x( )e

and

dt = d

j ( +t0 )

= e j t 0

x( )e

= e jt0 X ( )

Fourier Transform
Let

y (t ) = x(t t0 )

Y ( ) = X ( )e jt0 = X ( ) e j X ( )e jt0
= X ( ) e j ( X ( )t0 )
Y ( ) e j Y ( ) = X ( ) e j ( X ( )t0 )
Therefore, the amplitude spectrum of the time shifted signal is the
same as the amplitude spectrum of the original signal, and the phase
spectrum of the time-shifted signal is the sum of the phase spectrum of
the original signal and a linear phase term.

Fourier Transform
Example:

Determine the Fourier transform of the following time


shifted rectangular pulse.
x(t)

a j 2
X ( ) = ha sinc
e
2
a

t
a

>> h=1;
>> a=1;
>> f=-3.5:0.01:3.5;
>> w=2*pi*f;
>> x=abs(h*a*sinc(w*a/(2*pi)).*exp(j*w*1/2));
>> subplot (2,1,1)
>> plot (w,x)
>> title ('|X(\omega)|')
>> xlabel('\omega')
>> xp=phase(h*a*sinc(w*a/(2*pi)).*exp(j*w.*1/2));
>> subplot (2,1,2)
>> plot (w,xp)
>> xlabel('\omega')
>> title ('phaseX(\omega)')

Fourier Transform
3. Time Scaling

x(t ) X ( )

If

x(at )

Proof:

Let

then

1
X( )
a
a

= at then

t = / a and dt = (1/ a)d

If , a>0 then

x(at )e

j t

If , a<0 then

dt =

x( )e

j
a

1
= X( )
a
a

1
d
a

x(at )e

j t

dt =

x( )e

1
a

j
a

1
d
a

x( )e

j
a

d =

1
X( )
a
a

Fourier Transform
if , x(t ) X ( ) then find the Fourier transform of the
following signals

Example.

1
X( )
2
2

a.

x( 2t )

b.

x(t / 5) 5 X (5 )

c.

x( 5(t 2))

Example:

1 j 2
X ( )e
5
5

Find the Fourier transform of the following signal.



X1( ) = sinc

a.

x1(t ) = (t )

b.

x2 (t ) = (5t )

X 2 ( ) =

1

X1( ) = sinc

5
5
5
10

c. x3 (t ) = (t / 5) X 3 ( ) = 5 X1(5 ) = 5sinc
0.4

Fourier Transform
4. Duality (Symmetry)
If x(t ) X ( ) then

X (t ) 2 x( )
Proof:

or

X (t ) x(f )

Since t and are arbitrary variables in the inverse Fourier


transform
x(t ) =

1
2

X ( )e

j t

we can replace with t and t with - to get


x( ) =

1
2

X (t )e

j t

dt

Therefore,
F {X (t )} =

X (t )e

j t

dt = 2 x( )

Fourier Transform
Similarly, if we can replace f with t and t with -f in the inverse
Fourier transform

x(t ) =

X (f )e

j 2 ft

df

j 2 ft

df

to get

x( f ) =

X (t )e

Therefore,

F {X (t )} = x(f )

Fourier Transform
Example:

x(t ) = (t ) X ( ) = 1 Applying symmetry property,

x(t ) = 1 X ( ) = 2 ( ) = 2 ( )
or

( ( ) is even function)

x(t ) = 1 X (f ) = (f ) = (f )

Example:
t
a
x(t ) = rect X ( ) = a sinc

a

2
ta


x(t ) = a sinc
X ( ) = 2 rect a = 2 rect a
2

Let

c=

a
2

then a = 2 c
1

x(t ) = a sinc ( ct ) X ( ) = 2 rect
= c rect 2 c
2
c

Fourier Transform
Time Reversal
If x(t ) X ( ) then
x(t ) X ( )

Proof:

Let t = . Then t = and

x( t )e jt dt =

x( )e

j ( )

dt = d

d = X ( )

Fourier Transform
Frequency Shifting
If x(t ) X ( ) then

x(t )e jct X ( c )
Proof:

x(t )e jct e jt dt =

x(t )e

j ( c )t

dt = X ( c )

Fourier Transform
Example:

Determine the Fourier transform of cos ct and sinct

x(t ) = cos ct =

1 j c t 1 j c t
e + e
2
2

X ( ) = [ ( c ) + ( + c )]

or
x(t ) = cos ct =

1 j c t 1 j c t
e + e
2
2

X (f ) =

1
[ (f fc ) + (f + fc )]
2

X(f)
1/2

-fc

fc

The phase spectrum is zero everywhere.

Fourier Transform
x(t ) = sinct =

x(t ) = sinct =

1 j c t 1 j c t
e e
2j
2j

X ( ) = j [ ( c ) ( + c )]

1 j c t 1 j c t
e e
2j
2j

X (f ) =

j
[ (f fc ) (f + fc )]
2

|X(f)|
1/2

-fc

(f)

fc

/2

fc
f

-fc
-/2

10

Fourier Transform
7. Modulation
If x(t ) X ( ) then
x(t )cos(ct )

1
[ X ( c ) + X ( + c )]
2

Proof:

x(t )cos( t )e

j t

dt =

x(t ) 2 e

jc t

+ e jct e jt dt

1
= x(t )e j ( c )t dt + x(t )e j ( +c )t dt
2

1
[ X ( c ) + X ( + c )]
2

Fourier Transform
8. Time Differentiation:
General case

If x(t ) X ( ) then

d n x(t )
( j )n X ( )
dt n

dx(t )
j X ( )
dt
Proof:

Taking the derivative of the inverse Fourier transform

x(t ) =
we obtain

Therefore

1
2

dx(t )
1
=
2
dt

X ( )e

j t

j X ( )e jt d

dx(t )
j X ( )
dt

11

Fourier Transform
9. Time Differentiation:
General case

If x(t ) X ( ) then

dX ( j )
tx(t ) j
d
Proof:

t n x(t ) j n

d n X ( )
d n

Taking derivative of Fourier Transform

X ( ) =

x(t )e

j t

dt

with respect to , we obtain

dX ( )
= ( jt ) x(t )e jt dt
d

tx(t ) j

Therefore

dX ( j )
d

Fourier Transform
10 Conjugate
If x(t ) X ( ) then

x * (t ) X * ( )
Proof:
*

x (t )e
*

j t

dt = x(t )e j ( )t dt = X * ( )

*
If x(t) is real x (t ) = x (t ) so that

X ( ) = X * ( )

12

Fourier Transform
11. Convolution
y (t ) Y ( )

If x(t ) X ( ) ,h(t ) H ( ) , and

y (t ) = h(t ) * x(t ) =

h( )x(t )d

Y ( ) = H ( )X ( )
Proof:
Y ( ) =

h( )x(t )d e

jt

dt

Interchanging the order of integration, we obtain

j
j

Y ( ) = h( ) x(t )e jt dt d Y ( ) = h( )X ( )e d = X ( ) h( )e d

= X ( )H ( )

Fourier Transform
12. Multiplication
If x1(t ) X1( ), and
x1(t ) x2 (t )

x2 (t ) X 2 ( )

1
1
X1( ) * X 2 ( ) =
2
2

X (v )X
1

( v )dv

or

x1(t ) x2 (t ) X 1(f ) * X 2 (f ) =

X (v )X
1

(f v )dv

13

Fourier Transform
13. Parsevals Theorem
If x1(t ) X1( ), then total normalized(based on one ohms
resistor) energy E of and x(t) is given by

E=

x(t ) dt =

1
2

X ( ) d =

X (f ) df

Proof

x(t ) dt =

1
x(t ) 2

x(t ) x * (t ) dt =

X ( )e
*

j t

d dt

Interchanging the order of integration, we obtain

Fourier Transform
Proof (cont)

x(t ) dt =

1
2

*
j t
X

(
)
x(t )e dt d

1
2

1
2

X ( )X ( )d
*

X ( ) d

14

You might also like